Cerebrovascular Accident Secondary to Paradoxical Embolism Following Arteriovenous Graft Thrombectomy - Jolina Pamela Santos; Zaher Hamadeh; Naheed Ansari (Case Reports in Nephrology)
Thrombectomy is a common procedure performed to declot thrombosed dialysis arteriovenous fistula (AVF) or arteriovenous graft (AVG). Complications associated with access thrombectomy like pulmonary embolism have been reported, but paradoxical embolism is extremely rare. We report a case of a 74-year-old black man with past medical history significant for end-stage renal disease (ESRD), atrial fibrillation on anticoagulation with warfarin, who presented to our hospital with lethargy, aphasia, and right-sided hemiparesis following thrombectomy of a clotted AVG. Computed tomography (CT) scan of brain showed a hypodensity within the left posterior parietal lobe. INR was 2.0 on admission. Echocardiogram revealed a normal sized left atrium with no intracardiac thrombus, and bubble study showed the presence of right-to-left shunting. These findings suggest that the stroke occurred as a result of an embolus originating from the AVG. Paradoxical cerebral embolism is uncommon but can occur after thrombectomy of clotted vascular access in ESRD patients. Clinicians and patients should be aware of this serious and potentially fatal complication of vascular access procedure.